Multielemental Analysis and In Vitro Evaluation of Free Radical Scavenging Activity of Natural Phytopigments by ICP-OES and HPTLC - Nandanwadkar, S. M.; Hurkadale, P. J.; Bidikar, C. M.; Godbole, M. M. (Frontiers in Pharmacology, 2021)
The phyto-pigments derived from ethnomedicinal plants employed as traditional medicines, appear to be the simplest alternative for artificial radical colorants. This can be because of persistent use of synthetic dyes and their harmful impacts linked to human lives as well as to the eco-system. The literature evidences clearly reveal the complications from growing demands of radical colorants from artificial origin. The planned analysis work, hence focuses on screening of the fundamental composition of phyto-pigments, obtained from plant sources by subtle technique of ICP-OES, with axial plasma combined with nebulizer motor-assisted gas flow approach, utilizing Microwave digestor for complete digestion of phyto-pigments, thereby establishing safety of the pigments being safe for consumption. Additionally, the observations from free radical scavenging activity using DPPH by HP-TLC, concluded that the natural pigments obtained from plant sources are rich in flavonoids with potent anti-oxidant property. Thus, an effort has been made through the developed ICP-OES methodology, to beat the distinct imprecise practice of food labeling, once natural pigments are utilized in variety of additives as food colorants with amounts of components detected as Arsenic, Lead and metal, within specified limits of FSSAI, demonstrate and establish safety of natural foodstuff agents, as compared over hazardous synthetic azo dyes.